Deprem'den Soma'ya: Yeni Bir Hayata Başlama Deneyimlerine ve Algılarına İlişkin Nitel Bir Çalışma. - KAYMAKCI, Yavuz Selim; ACA, Zeynep (Journal of Society & Social Work / Toplum ve Sosyal Hizmet)
The study aimed to examine the experiences and perceptions of earthquake victims who permanently relocated after the February 6, 2023, Kahramanmaraş earthquake to start a new life. Utilizing the purposeful sampling technique, we interviewed fourteen earthquake victims who settled in Soma in the study employing a case study design. Semi-structured interviews, recorded upon the participants' consent, were held face-to-face between July 15 and September 20, 2023, and then transcribed. Our analyses revealed the following eight themes with their sub-themes: changing daily routine, economic difficulties, difficulties related to working life, psychological difficulties, difficulties encountered in health, difficulties encountered in education, negative interactions, and positive interactions. While the study is particularly relevant to the life experiences of those permanently displaced due to earthquakes, this experience caused by the earthquake implied the findings 'applicability to earthquake-related life experiences and permanent displacement experiences due to other disasters. As the research examined the experiences of earthquake victims from their perspective, it may guide the development of programs for further practices and prepare contingency plans in emergencies.